If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -10x = 106 + -45x Solving 11 + -10x = 106 + -45x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '45x' to each side of the equation. 11 + -10x + 45x = 106 + -45x + 45x Combine like terms: -10x + 45x = 35x 11 + 35x = 106 + -45x + 45x Combine like terms: -45x + 45x = 0 11 + 35x = 106 + 0 11 + 35x = 106 Add '-11' to each side of the equation. 11 + -11 + 35x = 106 + -11 Combine like terms: 11 + -11 = 0 0 + 35x = 106 + -11 35x = 106 + -11 Combine like terms: 106 + -11 = 95 35x = 95 Divide each side by '35'. x = 2.714285714 Simplifying x = 2.714285714
| 3(x+1)=7(x-2)+7 | | 254-4x=41x+24 | | 6x+3x^2+4x^3+x^4-10=0 | | 6-5x+3x^2+4x^3+x^4-10=0 | | 48585885858558585858x=838384744474484 | | x^2+5x=7 | | x-0.8x=20 | | 10(x+5)=5(x+15) | | 2x=40-6x | | 4x-8=52-8x | | 10x+4=4x+40 | | 119-4x=23+20 | | ln(7x-3)=3 | | 8x-32y=64 | | 4(3x+2)+4=9x+3 | | 17x-8y=323 | | 3ab+7ab-ab= | | 6-9x=14-6x | | 4x^2-x+7=7x+4 | | -9*9= | | 9*-9= | | (3x+52)=36 | | 58-6x=7x | | 6x+12=3(2x+4) | | 9y+3-5y=23 | | 6t-14=-10+5t | | 4x+8-12x=5x-(3x+2) | | 3q^2+4q=-2 | | 2x-6y=24whatisy | | 9m+18= | | 2x-6y=24 | | 3t-24=-24+8t |